IN VIVO EVALUATION OF CHITOSAN–TRICALCIUM PHOSPHATE BIOACTIVE COATING FOR ENHANCED OSSEOINTEGRATION OF TITANIUM DENTAL IMPLANTS - Ачилова Н.Г (TADQIQOTLAR, 2026)
Abstract The increasing prevalence of partial and complete edentulism necessitates the development of advanced implant systems capable of improving osseointegration and long-term clinical outcomes. Surface modification of titanium implants using bioactive materials  represents  a  promising  strategy  for  enhancing  biological  integration.This study  aimed  to  experimentally  evaluate  the  osteointegrative  effectiveness  and biocompatibility  of  a  novel  bioactive  coating  based  on  tricalcium  phosphate  and chitosan for domestically manufactured dental implants.An in vivo experimental study was  conducted  using  72  chinchilla  rabbits  divided  into  three  groups:  commercial implants, uncoated domestic titanium implants, and domestic implants coated with a bioactive  polymer  matrix.  Radiological,  densitometric,  histomorphological,  and biochemical analyses were performed at different postoperative periods.The developed coating demonstrated nanoscale morphology and stable adhesion to titanium surfaces. Experimental implants with bioactive coating exhibited accelerated bone regeneration, increased peri-implant bone density, and improved trabecular organization compared with uncoated implants. Positive osteointegration dynamics became evident after the first postoperative month.